2020
DOI: 10.1109/access.2020.2998635
|View full text |Cite
|
Sign up to set email alerts
|

CDED-Net: Joint Segmentation of Optic Disc and Optic Cup for Glaucoma Screening

Abstract: Glaucoma is an eye disease that can cause loss of vision by damaging the optic nerve. It is the world's second leading cause of blindness after cataracts. Early diagnosis of glaucoma is a key to prevent permanent blindness as it has no noticeable symptoms in its early stages. Color fundus photography is used for examining the optic disc (OD) which is an important step in the diagnoses of glaucoma. This is done by estimating the cup-to-disc ratio (CDR). In this paper, we proposed a Cup Disc Encoder Decoder Netw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 59 publications
(29 citation statements)
references
References 58 publications
1
24
0
Order By: Relevance
“…Consequently, the acquired datasets are preprocessed to enhance their quality. Next, segmentation techniques are utilized to extract the foreground from the background pixels based on their distinguishable characteristics, e.g., color, texture and shape [24]- [26]. Lastly, WBCs are distinguished from RBCs through classifiers whereby the presence of nucleus is first determined from the color information of the cells.…”
Section: Methodsmentioning
confidence: 99%
“…Consequently, the acquired datasets are preprocessed to enhance their quality. Next, segmentation techniques are utilized to extract the foreground from the background pixels based on their distinguishable characteristics, e.g., color, texture and shape [24]- [26]. Lastly, WBCs are distinguished from RBCs through classifiers whereby the presence of nucleus is first determined from the color information of the cells.…”
Section: Methodsmentioning
confidence: 99%
“…In [36], joint segmentation of OD and OC is formulated as a semantic pixel-wise labeling problem. An encoderdecoder network called Cup Disc Encoder Decoder Network (CDED-Net) based on the fully connected SegNet [37] architecture is proposed, employing feature information reuse to bridge the semantic gap between the features shared between the encoder and decoder blocks.…”
Section: Related Workmentioning
confidence: 99%
“…Precision = T P T P + FP (7) iii) Recall is the ratio of TP and the correct pixels in OD according to ground truth.…”
Section: Evaluation Metricsmentioning
confidence: 99%
“…The study confirmed that the accurate segmentation process of OD and OC jointly is essential to glaucoma detection and diagnosis. The authors of [7] leveraged the multi-task learning and dense connections to segment the OD and OC jointly. They evaluated their work on three datasets: DRISHTI-GS, RIM-ONE, and REFUGE.…”
Section: Introductionmentioning
confidence: 99%